Texture-based Multimode Analysis For Preliminary Diagnosis Of Liver Cyst And Fatty Liver Using Neural Networks - Chung, Sheng Hung (2007)
Medical imaging has become the most prominent technique in identifying diseases. For the diagnosis of liver diseases, patient usually undergo a series of examination, where a number of imaging techniques are employed. The popular medical imaging modalities for this include Magnetic Resonance Imaging (MRI), Ultrasound and Computed Tomography (CT) scans. The objective of this research is to develop semi-automated multimodality image analysis for preliminary diagnosis of liver diseases specifically cyst and fatty liver.